(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Management decision is the main activity of a manager. It creates the direction, form and content of the work of a collective of subordinates. The smallest gaps in management decisions can result in losses both for the employees of the workforce and, ultimately, for society.